A regulação da atividade de trabalho na produção enxuta - Silva, Elaine Cristina (Universidade Federal de São Carlos, 2011)
The use of lean manufacturing principles and techniques has been increasing considerably in companies over the past couple of decades. The employment of such techniques prompts profound transformations on both the project and work organization of the company that chooses to employ them. By this approach, companies that embrace the lean manufacturing model gain flexibility, acquire new principles, and adopt new techniques which enhance their manufacturing process management as well as their workforce management, supported upon the motivation of the worker as he performs his activities, upon team-work, and stimulated by qualification and engagement at work. The objective of this study is to deepen the knowledge of how workmen develop strategies and regulate work activities in productive situations that are planned and managed through principles and techniques based upon the lean manufacturing concept. In order to more clearly analyze the theme studied, a case study was conducted in the assembly line of a company that incorporated the lean manufacturing model to manage its manufacturing process. Work was analyzed through the analysis of activity, based on the precepts of the Ergonomic Analysis of Work. The case study certified that many aspects of the traditional assembly line remain evident in the lean assembly line; however, a new language is employed, due to the new culture and the more flexible model of lean manufacturing. Within the work situations that were analyzed in the case study, it was possible to establish some relevant aspects in the nature of regulations in which their relation to the lean techniques influence the strategies and operational modes of the workers during the process. Despite the diminishment of regulated space which takes place due to the application of lean manufacturing techniques, the operators continue to regulate work activities and fulfil production goals.
Keywords: Ergonomia; Produção enxuta; Regulação do trabalho; Análise ergonômica do trabalho; Modo operatório; Carga de trabalho; Estratégia operatória; Lean manufacturing; Ergonomics; Ergonomic analysis of work; Work activity regulation; Workload; Operational strategy; Operational mode; ENGENHARIAS::ENGENHARIA DE PRODUCAO